Pengaruh Electronic Word of Mouth (E-Wom) pada Media Sosial Terhadap Keputusan Orang Tua di Tha Chamuang Memilih Sekolah Darul Mahdiyah (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The increasing use of social media as a source of information has changed the way parents obtain information and determine school choices, so that Electronic Word of Mouth (e-WOM) has become one of the factors suspected of influencing these decisions. This study aims to analyze the influence of Electronic Word of Mouth (e-WOM) on parents' decisions in choosing Darul Mahdiyah School in Tha Chamuang, Southern Thailand. The study used a quantitative approach with a survey method. The study population was 820 parents, while a sample of 89 respondents was determined using a purposive sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression analysis, coefficient of determination (R²) test, and significance test with the help of IBM SPSS. The results showed that Electronic Word of Mouth (e-WOM) had a positive and significant effect on parents' decisions in choosing schools with a significance value of 0.000 (